1992
DOI: 10.4037/ajcc1992.1.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of ICU patients

Abstract: Critical care medicine programs must provide outpatient experience for their fellowship trainees. We have developed an unusual follow-up plan allowing critical care fellows to contact their patients months after their intensive care unit stay. We evaluated responses of 46 patients after a mean interval of 8.6 months since their initial intensive care unit stay. Patients were stratified by severity of disease by using the APACHE scoring system. Diagnostically, the patients represented the typical medical-surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The aim of these meetings would be to provide a forum for groups of patients to discuss their experiences. As observed by Friedman (1992), follow‐up clinics not only help patients but also assist staff morale by providing invaluable feedback. Such feedback also raises awareness of patients' perceptions of both ICU itself and the behaviour of the staff.…”
Section: Discussionmentioning
confidence: 94%
“…The aim of these meetings would be to provide a forum for groups of patients to discuss their experiences. As observed by Friedman (1992), follow‐up clinics not only help patients but also assist staff morale by providing invaluable feedback. Such feedback also raises awareness of patients' perceptions of both ICU itself and the behaviour of the staff.…”
Section: Discussionmentioning
confidence: 94%
“…Patients and their families and friends who experience difficulties during recovery after critical illness can be offered assistance, rehabilitation or referral to other services through an ICU follow-up service. Several authors have identified the need for such follow-up services to address uncertainties about functional ability or gaps in memory regarding the ICU stay (Friedman 1992, Hall-Smith et al 1997. Some hospitals in the United Kingdom, New Zealand and Australia have established follow-up clinics for people who have had an ICU stay as part of their hospital episode (Daffurn et al 1994, Jones et al 1994, Waldmann & Gaine 1996 , Broomhead & Brett 2002, Moran et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and their families and friends who experience difficulties during recovery after critical illness can be offered assistance, rehabilitation or referral to other services through an ICU follow‐up service. Several authors have identified the need for such follow‐up services to address uncertainties about functional ability or gaps in memory regarding the ICU stay (Friedman 1992, Hall‐Smith et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Patients continue to suffer nightmares and sleep deprivation for years following a critical illness. In a survey carried out with 46 ICU patients following discharge, 46% contacted after a mean of 8 months reported sleep disturbance and ICU-related dreams (Freidman et al, 1992).…”
Section: The Legacy Of Icumentioning
confidence: 99%